2013
DOI: 10.1111/vco.12045
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of baseline absolute lymphocyte concentration and neutrophil/lymphocyte ratio in dogs with newly diagnosed multi‐centric lymphoma

Abstract: Canine multi-centric B-cell lymphoma shares similarities with diffuse large B-cell (Non-Hodgkin's) lymphoma (NHL) in people. In people with NHL, lymphopenia at diagnosis and first relapse and neutrophil/lymphocyte ratio (N:L) > 3.5 are negative prognostic factors for survival. The objective of this study was to determine if lymphocyte concentration at diagnosis and first relapse and N:L were prognostic for survival in dogs with newly diagnosed multi-centric lymphoma. Medical records of 77 dogs with multi-centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 45 publications
5
59
2
Order By: Relevance
“…The median absolute lymphocyte concentration was 1176 cells/µl (ranged between 0-12376 cells/µl; reference range: 1000-4800 cells/µl; Mutz et al, 2015). Eighteen dogs had a lymphocyte count < 1000 cells/µl.…”
Section: Patient Characteristics and Cut-off Point Determinationmentioning
confidence: 99%
“…The median absolute lymphocyte concentration was 1176 cells/µl (ranged between 0-12376 cells/µl; reference range: 1000-4800 cells/µl; Mutz et al, 2015). Eighteen dogs had a lymphocyte count < 1000 cells/µl.…”
Section: Patient Characteristics and Cut-off Point Determinationmentioning
confidence: 99%
“…Lymphoma accounts for approximately 7-24% of all canine neoplasias and 83% of all canine haematopoietic malignancies (Kaiser, 1981;Moulton and Harvey, 1990). Numerous chemotherapeutic protocols for treating canine lymphoma have been developed over the past 40 years including the multiagent CHOP-based (C-cyclophosphamide; H-hydroxydaunorubicin; O-vincristine; P-prednisolone) protocol, and complete remission rates of 73-92% with median first remission duration (FRD) ranging from 8 to 12 months have been reported (Garrett et al, 2002;Rassnick et al, 2007;Burton et al, 2013;Mutz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2014. Recently, a study investigating the NLR in dogs with multi-centric lymphoma found that it was not a significant prognostic variable (Mutz et al . 2013 ), although patient numbers were small in comparison to human studies.…”
Section: Introductionmentioning
confidence: 99%